Delayed immune-related adverse events profile associated with immune checkpoint inhibitors: a real-world analysis - Yang, Yana; Li, Linman; Tian, Jing; Ma, Linwen; Wu, Yaoxin; Luo, Qian; Luo, Yan (Frontiers in Pharmacology, 2024)
Immune-related adverse events (irAEs) typically occur within 3 months of initiating immune-checkpoint inhibitors (ICIs), which has been extensively documented. But the clinical profiles of late-onset irAEs remain inadequately characterized. Therefore, this study aims to quantify the correlation between delayed irAEs and ICIs, and to delineate the profiles of delayed toxicities associated with ICIs using data from the Food and Drug Administration Adverse Event Reporting System (FAERS). Methods: Data from the January 2011 to December 2023 in FAERS database were extracted. Four signal detection indices, reporting odds ratio (ROR), proportional reporting ratio (PRR), Bayesian confidence propagation neural network (BCPNN) and multi-item gamma Poisson shrinker (MGPS), were employed to evaluate the associations between ICIs and delayed irAEs. Results: A total of 147854 cases were included in this study, of which 3738 cases related to delayed irAEs were identified. Generally, 8 signals at System Organ Class (SOC) level were found to be associated with ICIs. Males had a slightly higher reporting frequencies for respiratory disorders (ROR975=0.95) and blood and lymphatic system disorders (ROR025=1.22), but lower reporting frequencies for immune system disorders (ROR025=1.16). Three monotherapy(anti-PD-1, anti-PD-L1 and anti-CTLA-4) were all associated with significant increasing gastrointestinal disorders (ROR025=1.66, 1.16, 1.99) and metabolism disorders (ROR025=2.26, 1.74, 3.13). Anti-PD-1 therapy exhibited higher rates of respiratory toxicities (ROR025=1.46 versus 0.82) and skin toxicities (ROR025=1.27 versus 0.94) compared with anti-CTLA-4 therapy. At PT levels, pneumonitis (ROR025: from 11.85 to 29.27) and colitis (ROR025: from 2.11 to 24.84) were the most notable PT signals associated with all three ICI regimens. For outcomes of delayed irAEs, gastrointestinal disorders showed the highest proportion (51.06%) of death. Conclusion: Our pharmacovigilance analysis indicates that a small percentage of patients receiving ICIs therapy experience delayed irAEs, which are challenging to manage and may result in severe consequences. Prompt identification and intervention of these delayed irAEs are crucial in clinical practice.